1982
DOI: 10.1056/nejm198206033062202
|View full text |Cite
|
Sign up to set email alerts
|

A Surgical Approach to the Treatment of Fetal Hydrocephalus

Abstract: Untreated fetal hydrocephalus results in gross cranial and facial abnormalities and profound brain damage. In an attempt to prevent both, a ventriculoamniotic shunt was implanted in a fetus with probable X-linked aqueductal stenosis and hydrocephalus. Performed at 24 weeks' gestation, the procedure used techniques similar to those used for intrauterine transfusion. After shunt placement, the fetal head size grew normally until after the 32d week, when the shunt failed. A cesarean delivery was performed at 34 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(57 citation statements)
references
References 5 publications
3
53
0
1
Order By: Relevance
“…Options at the time of an in utero diagnosis of severe hydrocephalus are currently limited to termination of the pregnancy or expectant management. Fetal shunt placement has been attempted, but technical issues with the shunt and mixed patient outcomes resulted in a moratorium on fetal percutaneous shunting in the United States since 1985 (4,5).…”
mentioning
confidence: 99%
“…Options at the time of an in utero diagnosis of severe hydrocephalus are currently limited to termination of the pregnancy or expectant management. Fetal shunt placement has been attempted, but technical issues with the shunt and mixed patient outcomes resulted in a moratorium on fetal percutaneous shunting in the United States since 1985 (4,5).…”
mentioning
confidence: 99%
“…The team from the Fetal Treatment Center team did not get discouraged by this outcome: the majority of patients with LUTO could be safely and effectively helped by shunt placement (Harrison et al, 1981a,b). At that time these shunts were also proposed for in utero treatment of hydrocephalus until experimental work in fetal sheep and monkeys showed that such a treatment was ineffective (Clewell et al, 1982). This is a good example of how, despite great initial enthusiasm, critical evaluation of results prompted reconsideration.…”
Section: Luto and Early Applications Of Shuntingmentioning
confidence: 99%
“…Because of poor postnatal neurologic outcomes, efforts were made in the 1980s to intervene prenatally in order to bypass the obstructed aqueduct by means of serial cephalocentesis [10] and ventriculoamniotic shunting [11,12]. Ventriculoperitoneal shunting in newborns dramatically improved survival [13].…”
Section: Fetal Intervention For Severe Hydrocephalusmentioning
confidence: 99%